Let's take it beyond the book - Abd Razak, Dzulkifli (2007)
IT was so simple, the message by Prof Muhammad Yunus, the 2006 Nobel Peace Prize winner, at the Tun Dr Ismail Memorial Lecture Series. It has been said many times before that we can never stop learning, but Yunus' words give it special meaning. And his lecture was delivered at a most appropriate forum — in conjunction with the 36th Convocation of Universiti Sains Malaysia. What is obvious is that a university degree does not guarantee a job, not anymore. There are other factors at play — many of which can be mitigated through a university education, and then there are some that cannot. From book lilies like What they did not teach at Harvard Business School, one gets the feeling that even education at the world's best institution may not be complete.